Digital climate advisory and bundled services (DCAS) tools landscape assessment for Vietnam - Le Thi Tam; Huong Nguyen Mai; Ngoc Bich Vu Thi; Giles, James Edward; Kim, Kwang Hyung; Swaans, Cornelis P.M. (2022)
This document is a long list of existing digital tools and platforms for selected value chains in Vietnam based on key characteristics, accomplishments, challenges and business models.